Advantages and disadvantage of Mutual Funds: A Review - Shah, Heer Manish (Innovative Research Thoughts, 2017)
Mutual funds may invest in many kinds of securities. Types of securities that a particular fund could invest in are set forth in fund's prospectus, a legal document that describes fund's investment objective, investment approach & permitted investments. Investment objective describes type of income/earnings that fund seeks. Eg. Capital appreciation fund generally looks to earn most of its returns from increases in prices of securities this holds, rather than from dividend or interest income. Investment approach describes criteria that fund manager uses to select investments for fund. A mutual fund's investment portfolio is continually monitored by fund's portfolio manager or managers.